Penerapan Praperadilan terhadap Problematika Penetapan Tersangka yang Tidak Memenuhi Dua Alat Bukti - Hapsari, Trisa Aprillia; Mulyana, Yusep (Universitas Batanghari Jambi, 2025)
This research aims to examine the application of pre-trial to the problem of determining suspects who do not meet the requirements of at least two valid evidences in accordance with the provisions of Article 183 and Article 184 of the Criminal Code. This problem often occurs in criminal law practice in Indonesia, where the suspect is determined without going through valid procedures and without sufficient evidence, thus potentially violating the principles of human rights and substantive justice. This research uses normative juridical methods with legislative, conceptual, and case approaches, which focuses on the analysis of written legal norms and their application in practice through the study of laws and regulations, legal theories, and court decisions. The scope of the research includes the study of the evidence system in criminal procedure law as well as the protection of the rights of suspects, with the research object in the form of positive legal provisions, the theory of the validity of evidence, and the application of progressive law in judge's decisions. The types of legal materials used include primary legal materials (laws and decisions), secondary (legal literature and scientific journals), and tertiary (legal dictionaries and encyclopedias). Data collection is carried out through literature and documentation studies, while the analysis technique of legal materials is carried out descriptively-analytically by interpreting legal norms and examining their application systematically and critically. Research results show that pre-trial has an important function as a judicial control mechanism for investigators' actions that are beyond their authority. The Constitutional Court's decision number 21/PUU-XII/2014 has expanded the pre-trial object including the validity of determining the suspect. Through case studies such as the Pegi Setiawan case, it is proven that pre-trial is effective in ensuring the protection of individual rights and preventing abuse of authority by law enforcement officers. Therefore, the determination of suspects must be carried out carefully and based on valid legal procedures so as not to harm justice and public trust in the legal system.